Judicial Ethics, Legal Reasoning, and the Validity of Court Decisions: The Paradox of Constitutional Adjudication in Indonesia - Umarwan Sutopo; Endrik Safudin; Kholili Badriza (Al-Syakhsiyyah: Journal of Law and Family Studies, 2026)
This study aims to analyze the correlation between ethical and non-ethical rulings in the Indonesian judicial system, particularly in light of Constitutional Court Decision No. 90/PUU-XXI/2023, which was upheld despite the judge’s ethical violations, as determined by the Constitutional Court’s Honorary Council. The research focuses on the inconsistency between legal norms and judicial practice regarding the implications of ethical violations for the validity of rulings. This study employs a doctrinal legal method with a jurisprudential, conceptual, and critical-analytical approach to legislation, court rulings, and the construction of legal and moral reasoning in judicial practice. Data were analyzed qualitatively through a normative interpretation of the relationship between ethical norms and the legal legitimacy of rulings. The results indicate that the relationship between ethical and non-ethical rulings is paradoxical: normatively, they are integrated, yet in judicial practice, they are treated as separate, meaning that ethical violations do not automatically invalidate legal rulings. This study confirms that ethical and non-ethical rulings rest on different bases of reasoning; thus, they do not directly validate one another, yet they still influence each other within the framework of legal legitimacy, certainty, and justice.